(untitled) (Journal of Plant Disease Sciences, 2019)
Powdery mildew of rose caused by Sphaerotheca pannosa var. rosae is one of the most important diseases, causes enormous losses about 70% both in terms of quality and quantity of rose (Coyier, 1983). Powdery mildew of rose which is first appears in the form of small grayish, white powdery coating of the pathogen, consists of mycelium and conidia. Newly unfolded leaves are more susceptible and found to be affected more; the disease affects all the aerial parts of the plant. The younger leaves gets curled, exposing the lower surface and such leaves are likely to be purplish than the normal leaves.